1988
DOI: 10.1111/j.1469-185x.1988.tb00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating Frequency and Fecundity in Insects

Abstract: Summary 1. The paper summarizes the published evidence on the relation between mating frequency and fecundity in insects. There is experimental evidence of varying quality for 63 species and non‐experimental evidence for about 60. 2. Repeated mating may be universally necessary for full fecundity and fertility in female insects (in species in which the females normally mate more than once). 3. The evidence is remarkably poor. We need more properly designed experiments (and not just observations of natural vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
258
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(262 citation statements)
references
References 159 publications
2
258
0
2
Order By: Relevance
“…However, the incidence of female multiple-mating was only 12.4% , suggesting that the male's presence effectively deters female remating and that sperm competition is not common. In contrast, most female insects mate with at least two males (Parker 1970a;Ridley 1988). The level of sperm competition may not be as high in blue crabs, because non-virgin females may be more difficult to find and mate with than virgins.…”
Section: Sperm Competition In Blue Crabsmentioning
confidence: 99%
“…However, the incidence of female multiple-mating was only 12.4% , suggesting that the male's presence effectively deters female remating and that sperm competition is not common. In contrast, most female insects mate with at least two males (Parker 1970a;Ridley 1988). The level of sperm competition may not be as high in blue crabs, because non-virgin females may be more difficult to find and mate with than virgins.…”
Section: Sperm Competition In Blue Crabsmentioning
confidence: 99%
“…In many, if not the majority of insect species, females mate with multiple males ( Ridley, 1988( Ridley, , 1990, although in most cases the adaptive significance of multiple mating is not as apparent for female as for males ( Bateman, 1948 ). Nevertheless, in a recent meta-analysis of fitness consequences from polyandry in insects, Arnqvist and Nilsson (2000) demonstrated that the average direct female fitness gain from multiple mating is substantial.…”
Section: How Signifi Cant Are Female Direct Benefi Ts Of Polyandry Inmentioning
confidence: 99%
“…This is a problem, as female direct benefits from multiple mating per se have been shown to be considerable ( Ridley, 1988;Arnqvist & Nilsson, 2000 ). For example, sperm replenishment may influence female reproductive output (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in different insect species that females may acquire increased fecundity as a by-product of multiple mating and sperm storage ability (reviewed by Ridley, 1988;Arnqvist & Nilsson, 2000). This may have different explanations but, in general, males may provide females with seminal substances that increase fertility, eggproduction rate and female life span (Arnqvist & Nilsson, 2000).…”
Section: What Drives the Co-evolution?mentioning
confidence: 99%